HUBUNGAN PENGGUNAAN SUNTIK KB 3 BULAN DENGAN GANGGUAN MENSTRUASI DI PRAKTEK MANDIRI BIDAN YASMITA NORA PEKANBARU - Qori Armiza Septia; Tharra Widadari Aldinda; Iznirrahma Hayati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Injectable contraception, especially 3-month injectable birth control, is very popular, but often causes side effects. Common side effects of DMPA injection contraceptives include menstrual disorders such as irregular bleeding or amenorrhea (no menstruation). In addition, users can experience headaches, give symptoms of depression in patients with a history of mood disorders, severe premenstrual syndrome (PMS), and a decrease in estradiol which can cause vaginal dryness, although this is rare (Qomariah Sartika, 2019). This research aims to determine the relationship between the use of 3-month injectable contraceptives and menstrual disorders in the Independent Practice of Midwife Yasmita Nora in 2023. This research uses an analytical survey method with a cross-sectional approach to understand this phenomenon. The study population consisted of 106 family planning acceptors who injected 3 months into the practice. Sampling used Total Sampling, resulting in 106 respondents according to the inclusion criteria. The independent variable is the use of 3-month injection contraceptives, while the dependent variable is menstrual disorders. Data was collected through questionnaires and analyzed using univariate analysis and chi-square test (α0.05). The results of the chi-square test show that there is a relationship between the use of 3-month contraceptive injections and menstrual disorders (0.009). It is expected for midwives to provide knowledge and counseling to prospective acceptors or new acceptors regarding side effects and risks that can occur after prolonged use.Keywords: Injectable contraception, use of injectable birth control, menstrual pattern disorders